2009
DOI: 10.1111/j.1742-4658.2009.06967.x
|View full text |Cite
|
Sign up to set email alerts
|

A role of miR‐27 in the regulation of adipogenesis

Abstract: Summary MicroRNAs (miRNAs) are involved in a plethora of important biological processes from embryonic development to homeostasis in adult tissues. Recently, miRNAs have emerged as a class of epigenetic regulators of metabolism and energy homoestasis. We have investigated the role of miRNAs in the regulation of adipogenic differentiation. In this report, we demonstrate that the miR-27 gene family is down-regulated during adipogenic differentiation. Over-expression of miR-27 specifically inhibits adipocyte form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
320
1
13

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 407 publications
(356 citation statements)
references
References 33 publications
(61 reference statements)
22
320
1
13
Order By: Relevance
“…111 The expression of miR-27 decreases during adipogenesis and, interestingly, was found to be increased in adipose tissue of obese mouse. Finally, significant correlation of the levels of differents miRNAs with metabolic parameters such as fasting plasma glucose or circulating leptin and adiponectin has also been reported, 112 highlighting the importance of these factors in the regulation of metabolism.…”
Section: Differentiation Of Preadipocytesmentioning
confidence: 99%
“…111 The expression of miR-27 decreases during adipogenesis and, interestingly, was found to be increased in adipose tissue of obese mouse. Finally, significant correlation of the levels of differents miRNAs with metabolic parameters such as fasting plasma glucose or circulating leptin and adiponectin has also been reported, 112 highlighting the importance of these factors in the regulation of metabolism.…”
Section: Differentiation Of Preadipocytesmentioning
confidence: 99%
“…It has been reported that miR-27 enhances differentiation of osteoblasts and strongly inhibits adipogenesis (Lin et al, 2009;Wang and Xu, 2010). MiR-27b is a regulatory hub in lipid metabolism through repressing critical regulators of lipid homeostasis, such as PPARα, HMGCR (Kida et al, 2011, Vickers et al, 2013.…”
Section: Discussionmentioning
confidence: 99%
“…또한, miR-26도 지방분화를 촉진한다고 알려져 있다 [14]. 이와는 반대로, let-7a와 miR-27은 C/EBPα와 PPARγ의 발현을 제어하여 지방분화를 억제시킨다 [11,15] (Fig. 1A).…”
Section: 서 론unclassified